Differences by Economic Status in Grade 3 Reading Performance: A Texas Multiyear Study - Jenny A. M. McGown; John R. Slate (Athens Institute for Education and Research, 2019)
In this investigation, differences in the reading performance as a function of degree of economic disadvantage for Texas Grade 3 students were examined. Data were obtained from the Texas Education Agency on all Texas Grade 3 students for the 2012-2013, 2013-2014, and 2014-2015 school years. In all analyses, statistically significant differences, with small to moderate effect sizes, were present in reading performance, as measured by the State of Texas Assessment of Academic Readiness, by student economic status. For all three Reading Reporting categories, a "stair-step of achievement effect" was present in that the greater the degree of poverty the lower student reading scores were. Analyses of passing standards revealed a similar pattern in that the greater the degree of poverty, the less likely students were to meet the passing standard. Suggestions for future research and implications for policy and practice were made